2012
DOI: 10.1155/2012/686108
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Albumin Nanoparticles for Enhanced Drug Delivery to Treat Breast Cancer: Preparation and In Vitro Assessment

Abstract: Most anticancer drugs are greatly limited by the serious side effects that they cause. Doxorubicin (DOX) is an antineoplastic agent, commonly used against breast cancer. However, it may lead to irreversible cardiotoxicity, which could even result in congestive heart failure. In order to avoid these harmful side effects to the patients and to improve the therapeutic efficacy of doxorubicin, we developed DOX-loaded polyethylenimine- (PEI-) enhanced human serum albumin (HSA) nanoparticles. The formed nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 41 publications
0
46
0
Order By: Relevance
“…Meanwhile, the adverse effects of drugs may be effectively eliminated by employing NPs as a drug carrier. Albumin NPs have become a promising carrier for drug delivery due to their merits in bioavailability, biocompatibility and biodegradability [15, 16]. It was reported that piceatannol-loaded albumin NPs were able to prevent vascular inflammation by targeting activated neutrophils adherent to inflamed endothelium [17].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the adverse effects of drugs may be effectively eliminated by employing NPs as a drug carrier. Albumin NPs have become a promising carrier for drug delivery due to their merits in bioavailability, biocompatibility and biodegradability [15, 16]. It was reported that piceatannol-loaded albumin NPs were able to prevent vascular inflammation by targeting activated neutrophils adherent to inflamed endothelium [17].…”
Section: Introductionmentioning
confidence: 99%
“…19 Owing to their high surface area-to-volume ratio, it is possible to achieve high ligand density on the surface for targeting purposes. In terms of composition, nanoparticles are comprised of mainly two parts: the core material and the surface modifier that may be engaged to change the physiochemical properties of the former.…”
Section: Characteristics Of Nanoparticlesmentioning
confidence: 99%
“…To date, some examples of what nanotechnology has enabled include the development of improved imaging techniques for higher sensitivity in detection of cancer and illness 2 , improved targeting of drug treatments 3 , decrease in the number of adverse effects of chemotherapy, and the enhanced effectiveness of other antineoplastic therapies such as cryotherapy 4 and ultrasound 5 . Outside of medicine, nanotechnology is also fueling developoments in agriculture 6 , energy 7 , electronics 8 , and many other fields.…”
Section: Introductionmentioning
confidence: 99%